Geographical distribution update of Triatoma dispar (Hemiptera: Reduviidae: Triatominae) in Ecuador - Vaca-Moyano, Franklin; Enríquez, Sandra; Arrivillaga-Henríquez, Jazzmin; Villacrés-Guevara, Ernesto; Araujo, Pablo; Benítez-Ortíz, Washington (Revista Colombiana de Entomología, 2017)
Were recorded for the first time Triatoma dispar species at an altitude of 1,200 masl in Milpe km 90, CantonSan Miguel de los Bancos, Province of Pichincha and its geographical distribution is updated in Ecuador. Triatomines were collected during a sandflies study (Leishmania vectors) in peridomestic areas and forest remnants. Milpe km 90 did not present clinical evidence or transmission of the Chagas disease or enzootic circulation of Trypanosoma cruzi; however is in an area of high epidemiological risk. The present work contributes to the inventory of the Ecuador triatomine fauna and updating geographical distribution of T. dispar, a wild species with vectorial potential, which has already colonized domestic and peridomestic environments in Esmeraldas and Loja.